Sober Ways, Politic Drifts and Amiable Persuasions; approaching the Information Highway from the Dusty Trail - Ken Hannigan (IASSIST Quarterly, 1995)
Sober Ways, Politic Drifts and Amiable Persuasions; approaching the Information Highway from the Dusty Trail